A Logical Framework for Trust-Related Emotions - Bonnefon, Jean-FranÃ§ois; Longin, Dominique; Nguyen, Manh Hung (Electronic Communications of the EASST, 2010)
Emotion and trust are two important concerns for the elaboration of interaction systems that would be closer and more attractive to their users, in particular by endowing machines with the ability to predict, understand, and process emotions and trust. This paper attempts to construct a common logical framework for the representation of emotion and trust. This logical framework combines a logic of belief and choice, a logic of time, and a dynamic logic. Using this common framework, we identify formal relations between trust and emotions, for which we also provide behavioral validation.